Tech Startup Ecosystem in West Bank and Gaza : Findings and Recommendations - World Bank (World Bank, Washington, DC, 2018)
Technology is one of the main drivers of productivity and economic growth. Developing countries have traditionally had difficulties in both developing technology and absorbing foreign technology. However, the recent emergence of tech startups present an opportunity. Tech start-ups are an effective a mechanism to both create local technology and absorb foreign technology. The objective of this report is to provide a better understanding of the status of start-up ecosystem in West Bank and Gaza, and provide policy recommendations for policy makers and other stakeholders who are interested in supporting the growth and sustainability of the ecosystem. The report is based on an in-depth survey of startups and supportive stakeholders of the ecosystem. The findings point out to an early stage start-up that is maturing. Skills, supportive infrastructure, finance pipeline, and community and networks are examined and gaps are identified. Policy recommendations to tackle these gaps are presented based on international practices.